Optimizing Primary Care, The Role of Early Diagnostic Interventions in General Medicine - Sikander, Bakhtawar; Bubree, Afrida Alam; Ali Haider , Hafiz Muhammad; Esther .N. Okpako; Wandala , Abali; Aaroon, Sammar (Indus Journal of Bioscience Research, 2025)
A large percentage of diagnostic interventions used in the primary care practice constitute diagnostic interventions that have been proven to be very basic in the primary care practice and outcome since diseases can be diagnosed and treated before they cause complications. It was quantitative, and it was used in the research of the effects of early diagnostic interventions on patient outcomes, efficiency, and cost-effectiveness in general medicine. The target population was the population of the general medicine patients in the primary healthcare centers in Punjab, Pakistan, and the study design was descriptive cross-sectional. Where there was simple random sampling, 250 patients who had previously used the early diagnostic services within the past year were subjected to the structured patient records and the standardized questionnaire in an attempt to acquire the information. Data analysis was done using SPSS version 27. The demographic and clinical characteristics were provided along with the descriptive statistics. To deal with the objectives, the independent samples t-test had demonstrated the statistically essential difference between the patient outcomes in favor of those who have passed the early diagnostics successfully (p < 0.01). The chi-square test showed that the reduction in the number of hospitalization instances was highly associated with the early diagnostic treatments (χ² = 15.62, p = 0.000). ANOVA = 8.47 and p = 0.01 or less displayed that the difference between the healthcare costs according to the time of diagnosis was significant (F = 8.47, p = 0.01 or less), and the costs of treatment were lower in the cases of early intervention groups. The characters explain the clinical and economical benefit of the special interest in the first flow of the diagnostics in the health care institutions of the low resource.